The Heterogeneous Impact of Inflation on Households Balance Sheets - Clodomiro Ferreira; José Miguel Leiva; Galo Nu\~no; Álvaro Ortiz; Tomasa Rodrigo; Sirenia Vazquez (Center for Economic Studies and ifo Institute (CESifo), 2023)
We identify and study analytically three key channels that shape how inflation affects wealth inequality: (i) the traditional wealth (Fisher) channel through which inflation redistributes from lenders to borrowers; (ii) an income channel through which inflation reduces the real value of sticky wages and benefits; and (iii) a relative consumption channel through which heterogeneous increases in the price of different goods affect people differently depending on their consumption baskets. We then quantify these channels during the 2021 inflation surge in Spain using detailed and high-frequency client-level data from one of the main commercial banks. The unexpected nature and temporary perception of the inflation shock in this particular period closely maps on to the assumptions behind our theoretical decomposition. Results show that the wealth and income channels are one order of magnitude larger than the consumption channel. Middle-aged individuals were largely unaffected by inflation, while older ones suffered the most. We find similar results when using representative surveys on households' wealth, income, and consumption.
Keywords: G51; D31; E31; 330; inflation inequality; net nominal positions; nominal wage rigidities